U.S.-European Interest Rate Linkage: A Time Series Analysis for West Germany, Switzerland, and the United States - Kirchgassner, Gebhard; Wolters, Jurgen (The Review of Economics and Statistics, 1987)
, , U.S.-European Interest Rate Linkage: A Time Series Analysis for West Germany, Switzerland, and the United States, The Review of Economics and Statistics, Vol. 69, No. 4 (Nov., 1987), pp. 675-684